Heterocyclic Aromatic Amines Heterocomplexation with Biologically Active Aromatic Compounds and Its Possible Role in Chemoprevention. (15th April 2013) - Woziwodzka, Anna; Gołuński, Grzegorz; Piosik, Jacek
Abstract : Food-borne heterocyclic aromatic amines (HCAs) are known mutagens and carcinogens present especially in Western population diet, which contains large amount of meat and its products. HCAs are capable of interacting with DNA directly through the formation of covalent adducts, however this process requires biological activation in liver, mainly by cytochrome P450 enzymes. This process may produce mutations and in consequence may contribute to the development of cancer. However, there are many studies showing that several biologically active aromatic compounds (BACs) may protect against genotoxic effects of HCAs. Direct interactions and noncovalent heterocomplexes formation may be one of the most important mechanisms of such protection. This work describes several BACs present in human diet, which are capable of molecular complexes formation with HCAs and protect cells as well as whole organisms against HCAs action.